Revisiting Vedic Pedagogies: Historical Perspectives on Teaching and Learning - Kumar Shah, Rajendra (Journal of Neonatal Surgery, 2024)
This study critically examines the instructional traditions of Vedic education by revisiting ancient pedagogical approaches to assess their enduring influence on contemporary educational thought. Grounded in the spiritual, philosophical, and cultural foundations of early Nepali civilization, Vedic pedagogy emphasized the holistic development of the learner through oral transmission, dialogic inquiry, and moral cultivation. Adopting a qualitative research design within an interpretivist paradigm, the study employs textual analysis of Vedic literature to investigate key pedagogical constructs such as oral instruction, reflective learning, and the guru - siṣya relationship. Thematic analysis reveals fundamental philosophical underpinnings embodied in practices such as sravaṇa (attentive listening), manana (critical reflection), and nidhidhy asana (contemplative assimilation). The findings provide valuable insights into the continuing relevance of Vedic educational principles in informing and enriching present-day pedagogical discourse. This study concludes that the instructional methods employed during the Early Vedic period - such as tapas (austerity or disciplined effort), textual recitation, textual comprehension, the conference method, and brahmaṇa-sanghas (scholarly assemblies) -retain significant pedagogical value in the contemporary context. These approaches remain highly pertinent to both school - level and higher education. Likewise, the pedagogical practices of the Later Vedic period - including practices such as renunciation and meditation, the question - answer method, oral instruction, practical assessments, independent study, and experiential learning through field visits - continue to hold considerable educational importance. Collectively, these time-honored methods offer meaningful potential for fostering the holistic development of learners in modern educational settings. At the same time, this study concluded that these instructional strategies promote holistic education by integrating intellectual, moral, and spiritual development. Practices like tapas and meditation foster self-discipline and reflective learning, while oral traditions enhance linguistic skills and knowledge retention. Interactive methods such as the conference and question-answer foster critical thinking and collaborative learning. Practical examinations, self-study, and field trips encourage experiential learning, learner autonomy, and real-world application, supporting lifelong learning.